Softskill Improvement Workshop and Millennial Generation Digital Literacy at SMK YP Fatahillah 2 Cilegon City, Banten Province - Reni Haerani; R Dewi Mutia Farida; Heny Fitriani; Rosdiana; Ahmad Sofan Ansor; Sumarno; Aam Amaliyah; Deti Kurniati (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The millennial generation faces an increasingly complex and ever-evolving environment, especially regarding digital technology and social interaction. The increase in soft skills and digital literacy is significant so that they can succeed in adapting well to this changing world. Workshop material includes understanding the importance of soft skills in the work environment and daily life. To analyze the impact of mild skill improvement such as interpersonal communication, collaboration, and creativity, as well as digital literacy, which includes the ability to use and analyze digital technology wisely. This community service activity aims to provide the millennial generation insight, knowledge, and skills in increasing soft skills such as communication effectiveness, teamwork, creativity, and digital literacy. The SMK Fatahillah 2 Cilegon City activity involved class XII students who became partners in community services. The Methods used are lectures, discussions, and an interactive approach involving participants in various activities, such as role-playing, simulations, and question-and-answer sessions. Completing the training has positively impacted the millennial generation’s development, where students could increase their insight into soft skills and digital literacy. They become better prepared for rapid changes, can take the initiative in learning, and have a higher awareness of security and privacy issues in the digital world. Increasing soft skills and digital literacy is necessary for the millennial generation to succeed in various aspects of life.